TINJAUAN YURIDIS KASUS KONTAMINASI SUSU FORMULA DALAM PERSPEKTIF PEMBINAAN DAN PENDIDIKAN KONSUMEN - Theresia L Pesulima (SASI, 2011)
This study aims to determine the consumer protection system containing legal certainty and transparency of information and access to information. This study is normative, a study that examines the legal provisions of positive law and legal principles. The data used are secondary data, data obtained through library research and research tools for obtaining secondary data obtained through the study of documents. The results show that the picture is not clear that information obtained by the public in the case of infant formula reflects that the system of consumer protection provisions contained in the Consumer Protection Act can’t be realized the government and the level of knowledge/education is uneven between urban communities and suburban/rural . As such, it needs continuous efforts in fostering a critical attitude to the public on the quality of food products so as to encourage the creation of an attitude of prudence consuming public in terms of food products, and the Government should have good communication skills with the public as consumers.